Preparation method of PAN-MOF porous material for activating peroxymonosulfate
Pan-MOF multi-porous materials prepared by polypropylene and sodium chloride pores combined with metal organic framework solves the problem of difficulty separation and recycling in wastewater treatment in wastewater treatment, improving mechanical strength and catalytic efficiency, realizing materials Long -term stable application.
Patent Information
- Application Number
- CN202411348991.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing PAN-MOF porous materials with activated persulfate are difficult to separate and recover in wastewater treatment, the catalyst cycle stability is low, and the mechanical strength is insufficient.
By polypropylene (PAN) and sodium chloride pores combined with metal organic framework (NH2-MIL-101 (FE)), prepare Pan-MOF polyitic materials with a three-dimensional porous structure, and by adjusting sodium chloride particles by regulating sodium chloride particles Dimensions and settlement time, control the pore size of the material, and introduce cross -linking agents and transition metals to improve mechanical strength and catalytic activity.
It improves the mechanical strength and cycle stability of the material, enhances the catalytic efficiency, simplifies the process of separation and recycling, prolongs the service life of catalysts, and is suitable for long -term applications.
Smart Images

Figure CN119371708A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous material preparation, and in particular to a method for preparing a PAN-MOF porous material of activated peroxymonosulfate. Background Art
[0002] Preparation method of PAN-MOF porous material activated by persulfate The PAN-MOF porous material was successfully prepared by polyacrylonitrile (PAN) and sodium chloride pore-forming method combined with metal organic framework (NH2-MIL-101 (Fe), MOF). The specific steps are as follows: weigh polyacrylonitrile (PAN) powder and dissolve it in dimethylformamide (DMF) to form solution a, then prepare solution b with ferric chloride hexahydrate and 2-aminoterephthalic acid, then add solution b to solution a, mix and heat and stir to react, and after the reaction, generate porous material by sodium chloride pore-forming technology. After washing and freeze-drying, PAN-MOF porous material was finally obtained.
[0003] The system has some defects, which are mainly reflected in the following points: Low catalyst cycle stability: After multiple cycles, the removal efficiency of the material will drop significantly, especially the efficiency of quinoline degradation will drop from 78.8% to 46.3%. This shows that in long-term application, the active center of the catalyst will gradually be lost. The mechanical strength of the material needs to be improved: Although the material can still maintain a good shape after the reaction, a small amount of debris falls off, which may affect the material's reusability and separation efficiency. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a PAN-MOF porous material of activated peroxymonosulfate, which solves the problem that Fe-MOF powder is difficult to separate and recover in wastewater treatment.
[0006] (II) Technical solution
[0007] To achieve the above objectives, the present invention is implemented by the following technical scheme: a method for preparing a PAN-MOF porous material activated with peroxymonosulfate, comprising:
[0008] A. Weigh 4.45g~8.18g of polyacrylonitrile powder into a 250mL blue-capped reagent bottle, add 30.0mL of N,N-dimethylformamide, and stir in a 60℃ oil bath until completely dissolved to obtain solution a;
[0009] B. Weigh 1.35 g of ferric chloride hexahydrate and 0.45 g of 2-aminoterephthalic acid, add 10.0 mL of N,N-dimethylformamide, and perform ultrasonic treatment until completely dissolved to obtain solution b;
[0010] C. Add solution b to solution a and stir until evenly mixed;
[0011] D. Place the mixed solution in a sealed oil bath at 110°C for 24 hours;
[0012] E. cooling the reaction product naturally to room temperature;
[0013] F. Pour the cooled product into a beaker, add sodium chloride evenly to the surface of the solution, and let it stand overnight for more than 4 hours to allow the sodium chloride to settle;
[0014] G. Soak the evenly distributed material in deionized water and cut it into strips to dissolve the sodium chloride and DMF. Repeat the washing several times until the sodium chloride and DMF are completely washed away;
[0015] H. placing the washed material in a freeze drying oven and freeze drying for 48 hours to obtain a PAN-MOF porous material;
[0016] I. Analyze the pore structure of PAN-MOF porous materials by scanning electron microscopy to ensure that it has a uniformly distributed pore structure;
[0017] J. Characterization of the crystal structure of PAN-MOF porous materials by X-ray diffractometry.
[0018] Preferably, the molecular weight of the polyacrylonitrile powder in step A is 150,000 to ensure that the material has appropriate mechanical strength and pore structure, and the molar ratio of ferric chloride hexahydrate to 2-aminoterephthalic acid in step B is 2:1 to optimize the formation and distribution of MOF.
[0019] Preferably, the reaction temperature in step D is 110° C. and the reaction time is 24 hours to ensure the complete formation of NH2-MIL-101(Fe), and the size range of the sodium chloride particles added in step F is 0.1 to 0.5 mm to control the pore size of the porous material.
[0020] Preferably, the natural sedimentation described in step F allows the sodium chloride to fully and evenly settle to the bottom to ensure that the sodium chloride is fully settled and forms uniform pores, and the number of deionized water washing in step G is at least 3 times to ensure that the sodium chloride and DMF are completely dissolved and washed.
[0021] Preferably, the freeze-drying temperature in step H is -50°C to ensure the integrity and stability of the material structure. The mechanical strength and cyclic stability of the PAN-MOF porous material are further improved by introducing a cross-linking agent into the pores.
[0022] Preferably, in the process of catalytic activation of peroxymonosulfate to remove methyl blue, the catalytic efficiency of the PAN-MOF material remains above 65% after four cycles of use. By introducing transition metal iron into the MOF material, its catalytic activity and mechanical strength are further enhanced.
[0023] Preferably, the pore size of the material is precisely controlled by adjusting the size and sedimentation time of sodium chloride particles, and the PAN-MOF porous material is used to remove a variety of organic pollutants in water, including methyl blue, quinoline and oily wastewater.
[0024] Preferably, the PAN-MOF material recovers its activity by simple water washing or ethanol washing after use, thereby extending the service life of the catalyst. The material still maintains high mechanical strength and structural stability after multiple reaction cycles and is suitable for long-term applications.
[0025] (III) Beneficial effects
[0026] The present invention provides a method for preparing a PAN-MOF porous material for activating peroxymonosulfate. The method has the following beneficial effects:
[0027] The present invention successfully synthesizes a PAN-MOF material with a three-dimensional porous structure through a PAN and sodium chloride pore-forming method. The material can not only effectively activate peroxymonosulfate to degrade a variety of pollutants, but also has significant mechanical strength and cyclic stability. By adjusting the size and sedimentation time of sodium chloride particles, the pore size of the material is precisely controlled, which not only improves its catalytic efficiency, but also makes the material easy to separate and recycle during use, reducing the loss problem during use. The introduced cross-linking agent and transition metal further enhance the catalytic activity and mechanical properties of the material, so that it can still maintain a high catalytic effect after multiple cycles.
[0028] The PAN-MOF porous material prepared by the present invention has the advantages of simple operation, low production cost, high recovery efficiency, etc., and is particularly suitable for the removal of organic pollutants in water bodies. Its macroscopic three-dimensional structure makes it easy to separate the material after sewage treatment, significantly shortens the material recovery time, and prolongs the service life of the catalyst. The catalytic efficiency of the material can still be maintained at a high level after multiple cycles, showing great potential in long-term applications, and is expected to be widely used in sewage treatment, environmental governance and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The following are photos and cross-sectional SEM images of the materials prepared in the present invention;
[0030] Figure 2 is an X-ray diffraction pattern of the PAN-MOF porous material prepared by the present invention;
[0031] Figure 3 The test results of PAN-MOF porous material activated PMS to remove methyl blue, quinoline and oily wastewater;
[0032] Figure 4 The cycle number diagram of PAN-MOF porous material activation of PMS to remove methyl blue and quinoline;
[0033] Figure 5 This is a comparison chart before and after the removal of methyl blue and oily wastewater by PAN-MOF porous materials. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Embodiment 1:
[0036] like Figure 1-4 The embodiment of the present invention provides a method for preparing a PAN-MOF porous material of activated persulfate, comprising: A. weighing 4.45 g to 8.18 g of polyacrylonitrile powder and pouring it into a 250 mL blue-capped reagent bottle, adding 30.0 mL of N,N-dimethylformamide, and stirring in a 60° C. oil bath until completely dissolved to obtain a solution, wherein the molecular weight of the polyacrylonitrile powder is 150,000, so as to ensure that the material has appropriate mechanical strength and pore structure.
[0037] B. Weigh 1.35g of ferric chloride hexahydrate and 0.45g of 2-aminoterephthalic acid, add 10.0mL of N,N-dimethylformamide, and ultrasonicate until completely dissolved to obtain solution b; the molar ratio of ferric chloride hexahydrate to 2-aminoterephthalic acid in this step is 2:1 to optimize the formation and distribution of MOF
[0038] C. Add solution b to solution a and stir until evenly mixed.
[0039] D. placing the mixed solution in a sealed oil bath at 110° C. for 24 hours, the reaction temperature is 110° C., and the reaction time is 24 hours to ensure the complete formation of NH2-MIL-101(Fe). The size of the sodium chloride particles added in step F ranges from 0.1 to 0.5 mm to control the pore size of the porous material;
[0040] E. Allow the reaction product to cool naturally to room temperature.
[0041] F. Pour the cooled product into a beaker, add sodium chloride evenly to the surface of the solution, and let it stand overnight for more than 4 hours to allow the sodium chloride to settle.
[0042] G. Soak the evenly distributed material in deionized water and cut it into strips to dissolve the sodium chloride and DMF. Repeat the washing several times until the sodium chloride and DMF are completely washed away. The number of deionized water washings is at least 3 times to ensure that the sodium chloride and DMF are completely dissolved and washed away.
[0043] H. The cleaned material was placed in a freeze drying box and freeze-dried for 48 hours to obtain PAN-MOF porous material. The freeze-drying temperature was -50°C to ensure the integrity and stability of the material structure. The mechanical strength and cyclic stability of the PAN-MOF porous material were further improved by introducing a cross-linking agent into the pores.
[0044] I. The pore structure of PAN-MOF porous material was analyzed by scanning electron microscopy to ensure that it has a uniformly distributed pore structure. At the same time, NH2-M IL-101(Fe) presenting regular hexagonal microspindle crystals was fixed on the PAN porous material to further enhance its catalytic activity and mechanical strength. The pore size of the material was precisely controlled by adjusting the size of sodium chloride particles and the sedimentation time. PAN-MOF porous material was used to remove a variety of organic pollutants from water, including methyl blue, quinoline and oily wastewater. After use, PAN-MOF material can be restored to its activity by simple water washing or ethanol washing to extend the service life of the catalyst. The material still maintains high mechanical strength and structural stability after multiple reaction cycles and is suitable for long-term applications.
[0045] Embodiment 2:
[0046] The crystal structure of PAN-MOF porous materials was characterized by X-ray diffraction ( Figure 2 ). In the figure, PAN is prepared by the same method as PAN-MOF porous material, but ferric chloride hexahydrate and 2-aminoterephthalic acid are not added during the synthesis process. It can be seen from the figure that PAN has an obvious characteristic peak at 2θ=16.8°, indicating that PAN is a hexagonal structure; there is a small diffraction peak at 2θ=29.2°, proving that PAN is an amorphous structure. It can be seen from the figure that PAN-MOF porous material has the characteristic peaks of PAN, and also has the characteristic peaks of NH2-M IL-101(Fe) at 2θ=9.20°, 10.2° and 29.3°, proving the successful synthesis of PAN-MOF porous material.
[0047] Embodiment 3:
[0048] PAN-MOF porous material activates PMS to remove methyl blue
[0049] In order to investigate the PMS activation performance of the prepared PAN-MOF porous material, methyl blue was selected as the research object, and its removal performance of methyl blue was determined. The test conditions were 0.1g PAN-MOF porous material, 1mM potassium persulfate (PMS) was added, 100mL of methyl blue solution with a mass concentration of 5mg / L was reacted at 25℃ for 3h, the absorbance of the solution was measured, and the concentration was calculated. The removal rate of methyl blue was calculated according to the following formula:
[0050]
[0051] Where C0 is the concentration of methyl blue solution before removal; C t is the concentration of the methylene blue solution after removal.
[0052] Comparative Example 1: Removal of Methyl Blue by PAN-MOF Porous Material Alone
[0053] Different from Example 3, only PAN-MOF porous material was added, 100 mL of methyl blue solution with a mass concentration of 5 mg / L was reacted at 25° C. for 3 h, and the absorbance of the solution was measured.
[0054] Comparative Example 2: Removal of Methyl Blue by PMS Alone
[0055] Different from Example 3, only 1 mM PMS was added, 100 mL of methyl blue solution with a mass concentration of 5 mg / L was reacted at 25° C. for 3 h, and the absorbance of the solution was measured.
[0056] The test results of the prepared PAN-MOF porous material activating PMS to remove methyl blue are shown in Figure 3 As shown, from Figure 3 It can be seen that after PAN-MOF porous material activated PMS for 3 hours, the removal rate of methyl blue was 100%, while the removal rates of PAN-MOF porous material or PMS alone were 11.7% and 11.5%, indicating that PAN-MOF porous material has a good removal effect on methyl blue after activation of PMS.
[0057] Example 4: PAN-MOF porous material activates PMS to remove quinoline
[0058] In order to investigate the activated PMS performance of the prepared PAN-MOF porous material, quinoline was selected as the research object, and its removal performance of quinoline was determined. The test conditions were 0.1g PAN-MOF porous material, 1mM PMS was added, 100mL of quinoline solution with a mass concentration of 10mg / L was reacted at 25℃ for 3h, and the concentration of the solution was determined by HPLC. The removal rate of quinoline was calculated according to the following formula:
[0059]
[0060] Where C0 is the concentration of quinoline solution before removal; C t is the concentration of quinoline solution after removal.
[0061] Comparative Example 3: Removal of quinoline by PAN-MOF porous material alone
[0062] Different from Example 4, only PAN-MOF porous material was added, 100 mL of quinoline solution with a mass concentration of 10 mg / L was reacted at 25° C. for 3 h, and the quinoline concentration was measured.
[0063] Comparative Example 4: Removal of quinoline by PMS alone
[0064] The difference from Example 4 is that only 1 mM PMS is added, 100 mL of quinoline solution with a mass concentration of 10 mg / L is reacted at 25° C. for 3 h, and the quinoline concentration is measured.
[0065] The test results of the prepared PAN-MOF porous material activating PMS to remove quinoline are as follows Figure 3 As shown. Figure 3 It can be seen that after PAN-MOF porous material activated PMS removal for 3 hours, the removal rate of quinoline was 78.8%, while the removal rates of PAN-MOF porous material or PMS alone were 30.9% and 22.6%, respectively, indicating that PAN-MOF porous material activated PMS has a good removal effect on quinoline.
[0066] Example 5: PAN-MOF porous material activated PMS to remove oily wastewater (emulsified oil washing)
[0067] In order to investigate the activated PMS performance of the prepared PAN-MOF porous material, oily wastewater was selected as the research object, and its removal performance of oily wastewater was determined. The test conditions were 0.1g PAN-MOF porous material, 1mM PMS was added, 100mL of oily wastewater solution with a mass concentration of 100mg / L was reacted at 25℃ for 3h, and the absorbance of the solution was determined. The removal rate of oily wastewater was calculated according to the following formula:
[0068]
[0069] Where C0 is the concentration of the oily wastewater solution before removal; C t is the concentration of oily wastewater solution after removal.
[0070] Comparative Example 5: Removal of Oily Wastewater by PAN-MOF Porous Material Alone
[0071] Different from Example 5, only PAN-MOF porous material was added, 100 mL of oily wastewater solution with a mass concentration of 100 mg / L was reacted at 25° C. for 3 h, and the absorbance of the solution was measured.
[0072] Comparative Example 6: Removal of Oily Wastewater by PMS Alone
[0073] Different from Example 5, only 1 mM PMS was added, 100 mL of the oily wastewater solution with a mass concentration of 100 mg / L was reacted at 25° C. for 3 h, and the absorbance of the solution was measured.
[0074] The test results of the prepared PAN-MOF porous material activating PMS to remove oily wastewater are as follows: Figure 3 It can be seen that after PAN-MOF porous material activated PMS removal for 3 hours, the removal rate of oily wastewater was 71.1%, while the removal rates of PAN-MOF porous material or PMS alone were 29.1% and 22.8%, respectively, indicating that PAN-MOF porous material activated PMS has a good removal effect on oily wastewater.
[0075] Depend on Figure 3 The results show that the present invention uses PAN-MOF porous materials to activate PMS, because the active metal sites in NH2-MIL-101(Fe) can interact with PMS more effectively, and can effectively activate PMS to produce SO4· - , OH and 1 Active substances such as O2 degrade pollutants.
[0076] Example 6: Stability and reproducible practicality assessment
[0077] In order to evaluate the potential of the material in practical applications, after removing methyl blue from the PAN-MOF porous material, the PAN-MOF porous material was taken out with tweezers and washed three times in anhydrous ethanol and water respectively, and then freeze-dried for 24 hours, and then used in the next cycle experiment (activating PMS to remove methyl blue). The results of the four cycles were: 100%, 94.6%, 73.2%, and 66.8%, respectively.
[0078] In order to evaluate the potential of the material in practical applications, after removing quinoline from the PAN-MOF porous material, the PAN-MOF porous material was taken out with tweezers and washed three times in anhydrous ethanol and water, and then freeze-dried for 24 hours before being used in the next cycle experiment (activating PMS to remove quinoline). Figure 4 It can be seen that the results of four cycles are: 78.8%, 70.5%, 51.2%, and 46.3%.
[0079] Example 7: Comparison of PAN-MOF porous materials before and after removal of methylene blue and oily wastewater,
[0080] from Figure 5 It can be seen that after removing methyl blue, the blue color of the solution faded; after removing the oily wastewater, the solution changed from turbid to clear, and the PAN-MOF porous material was not broken, only a small amount of debris fell off, and the overall shape was the same as before the reaction, indicating that this porous material is strong and not easy to disperse. At the same time, this material is easy to separate and recover after the reaction.
[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a PAN-MOF porous material activated with peroxymonosulfate, characterized in that: include: A. Pour 4.45g~8.18g of polyacrylonitrile powder and 30mL of N,N-dimethylformamide into a 250mL blue-capped reagent bottle and stir in a 60℃ oil bath until completely dissolved to obtain solution a; B. Weigh 1.35 g of ferric chloride hexahydrate and 0.45 g of 2-aminoterephthalic acid, add 10.0 mL of N,N-dimethylformamide, and perform ultrasonic treatment until completely dissolved to obtain solution b; C. Add solution b to solution a and stir until evenly mixed; D. Place the mixed solution in a sealed oil bath at 110°C for 24 hours; E. cooling the reaction product naturally to room temperature; F. Pour the cooled product into a beaker, add sodium chloride evenly to the surface of the solution, and let it stand overnight for more than 4 hours to allow the sodium chloride to settle; G. Soak the settled material in deionized water and cut it into strips to dissolve sodium chloride and DMF, and repeat the washing several times until the sodium chloride and DMF are completely washed away; H. placing the washed material in a freeze drying oven and freeze drying for 48 hours to obtain a PAN-MOF porous material; I. Analyze the pore structure of PAN-MOF porous materials by scanning electron microscopy to ensure that it has a uniformly distributed pore structure; J. Characterization of the crystal structure of PAN-MOF porous materials by X-ray diffractometry.
2. The method for preparing a PAN-MOF porous material for activated peroxymonosulfate according to claim 1, characterized in that: The molecular weight of the polyacrylonitrile powder in step A is 150,000 to ensure that the material has appropriate mechanical strength and pore structure, and the molar ratio of ferric chloride hexahydrate to 2-aminoterephthalic acid in step B is 2:1 to optimize the formation and distribution of MOF.
3. The method for preparing a PAN-MOF porous material for activated peroxymonosulfate according to claim 1, characterized in that: The reaction temperature in step D is 110° C. and the reaction time is 24 hours to ensure the complete formation of NH 2 -MIL-101(Fe). The size of the sodium chloride particles added in step F ranges from 0.1 to 0.5 mm to control the pore size of the porous material.
4. The method for preparing a PAN-MOF porous material for activated peroxymonosulfate according to claim 1, characterized in that: The natural sedimentation described in step F allows the sodium chloride to fully and evenly settle to the bottom to ensure that the sodium chloride is fully settled and forms uniform pores. The number of deionized water washing in step G is at least 3 times to ensure that the sodium chloride and DMF are completely dissolved and washed.
5. The method for preparing a PAN-MOF porous material for activated peroxymonosulfate according to claim 1, characterized in that: The freeze-drying temperature in step H is -50°C to ensure the integrity and stability of the material structure. The mechanical strength and cycle stability of the PAN-MOF porous material are further improved by introducing a cross-linking agent into the pores.
6. The method for preparing a PAN-MOF porous material activated with peroxymonosulfate according to claim 1, characterized in that: In the process of catalytic activation of peroxymonosulfate to remove methyl blue, the catalytic efficiency of the PAN-MOF material is maintained above 65% after being recycled four times. The catalytic activity of the MOF material is further enhanced by introducing transition metal iron into the MOF material.
7. The method for preparing a PAN-MOF porous material for activated peroxymonosulfate according to claim 1, characterized in that: The pore size of the material is precisely controlled by adjusting the size and sedimentation time of sodium chloride particles. The PAN-MOF porous material is used to remove a variety of organic pollutants in water, including methyl blue, quinoline and oily wastewater.
8. The method for preparing a PAN-MOF porous material for activated peroxymonosulfate according to claim 1, characterized in that: The PAN-MOF material can restore its activity through simple water washing or ethanol washing after use, thereby extending the service life of the catalyst. The material still maintains high mechanical strength and structural stability after multiple reaction cycles and is suitable for long-term applications.
Citation Information
Patent Citations
Copper-manganese-doped iron metal organic framework material, preparation method thereof and method for treating organic wastewater by catalytically activating persulfate
CN113351254A
Metal organic framework-ferroferric oxide magnetic fiber composite material and in-situ preparation method thereof
CN117488415A
Bipolar membrane containing MOF (Metal Organic Framework) catalyst middle layer as well as preparation method and application of bipolar membrane
CN118286869A
Process for preparing metal organic frameworks having improved water stability
US20210268476A1
Charged membranes incorporated with porous polymer frameworks
US20230390708A1